2021
DOI: 10.1002/adfm.202108350
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Titanates: Classification, Property, Preparation, and Sustainable Energy Catalysis

Abstract: Global warming, energy deficiency, and environmental deterioration triggered by burning fossil fuels, may severely impair economic development and human life and health. Green solar power, mechanical energy, and temperature fluctuation heat energy abound in nature and are readily accessible. Thanks to various appealing characteristics, titanates are universally employed to harvest these sustainable energy sources to produce renewable fuels through photocatalysis, piezocatalysis, and pyrocatalysis, alleviating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 354 publications
(352 reference statements)
0
7
0
Order By: Relevance
“…Crystal structures of several typical such TMOs are presented in Figure 4. [64][65][66][67][68] Manganese dioxide (MnO 2 ) has six common crystal structures: hollandite-type MnO 2 (α-MnO 2 ), pyrolusite-type MnO 2 (β-MnO 2 ), nsutite-type MnO 2 (γ-MnO 2 ), birnessite-type MnO 2 (δ-MnO 2 ), hausmannite-type MnO 2 (λ-MnO 2 ), and ramsdellite-type MnO 2 (R-MnO 2 ). [69,70] Among them, the MnO 6 octahedron, in which Mn 4+ is surrounded by six oxygen atoms, is the basic building unit, which can combine into 1D (α-, β-, γ-, and R-MnO 2 ), 2D (δ-MnO 2 ), and 3D (λ-MnO 2 ) tunnel structures by sharing vertices and edges, corresponding to different crystal structures.…”
Section: D Tmosmentioning
confidence: 99%
“…Crystal structures of several typical such TMOs are presented in Figure 4. [64][65][66][67][68] Manganese dioxide (MnO 2 ) has six common crystal structures: hollandite-type MnO 2 (α-MnO 2 ), pyrolusite-type MnO 2 (β-MnO 2 ), nsutite-type MnO 2 (γ-MnO 2 ), birnessite-type MnO 2 (δ-MnO 2 ), hausmannite-type MnO 2 (λ-MnO 2 ), and ramsdellite-type MnO 2 (R-MnO 2 ). [69,70] Among them, the MnO 6 octahedron, in which Mn 4+ is surrounded by six oxygen atoms, is the basic building unit, which can combine into 1D (α-, β-, γ-, and R-MnO 2 ), 2D (δ-MnO 2 ), and 3D (λ-MnO 2 ) tunnel structures by sharing vertices and edges, corresponding to different crystal structures.…”
Section: D Tmosmentioning
confidence: 99%
“…The developments of the secondary phase indicate the solid solubility limit of Nd 0.33 NbO 3 in the 0.94Bi 0.5 Na 0.5 TiO 3 -0.06BaTiO 3 system of about 2 mol%. Previous studies also demonstrated the appearance of this Bi 2 Ti 2 O 7 secondary phase in Bi 0.5 Na 0.5 TiO 3 -BaTiO 3 -based ceramics (Ding et al, 2022;Lu et al, 2011;Ni et al, 2012;Wang et al, 2022). This secondary phase Bi 2 Ti 2 O 7 appeared due to the vaporization of Bi and Na at elevated temperatures (Xu et al, 2015).…”
Section: Phases and Microstructures Interpretationmentioning
confidence: 61%
“…As reported in the literature, LaCrO 3 is not an efficient photocatalyst because it exhibits intrinsic high charge carrier recombination that severely restricts quantum efficiency, leading to a decrease in HER performance. 46,47 According to our data, creating oxygen vacancies by topotactic reduction favors the separation of electrons from holes, thereby enhancing the photocatalytic HER performance of LaCrO 3 -based materials. This method provides an alternative to the usual doping of A and B sites in perovskite oxide-based materials.…”
Section: Resultsmentioning
confidence: 98%